Monoamine oxidase and α-synuclein as targets in Parkinson's disease therapy. (June 2014) - Follmer, Cristian
Abstract : The degeneration of dopaminergic neurons in Parkinson's disease (PD) is suggested to be associated with the generation of cytotoxic products from dopamine (DA) metabolism and the formation of fibrillar inclusions of the protein α-synuclein (AS). Despite of the role of AS in the pathogenesis of PD is not completely understood, the stabilization of nontoxic aggregates could represent a potential therapeutic route. In respect to the DA metabolism, a well-established strategy is the inhibition of the enzyme monoamine oxidase, which is responsible to catalyze the major route of inactivation of neurotransmitters. Although pharmacological strategies to treat different aspects of the parkinsonian condition are under investigation, the development of multifunctional molecules that act simultaneously on different targets associated to PD has gained attention only recently. In this work we examine the biochemical properties of synthetic and natural molecules that are capable of interfering on both DA system (via monoamine oxidase inhibition) and AS fibrillation.